More injury stoppage time in women compared to men in elite level football tournaments: Retrospective comparison of match injuries in 2018 FIFA Men`s World Cup and 2019 FIFA Women`s World Cup - Dönmez, G.; Ilicepinar, Ö. F.; Torgutalp, S. S.; Chamari, K. (Biology of Sport, 2025)
To identify the incidence of injury time-out due to field injuries in highest level professional football (soccer) international tournaments and to compare the features of these incidents between men`s and women`s football. The incidence of stoppage time due to incidents and the resulting injury characteristics of professional football players participating in the 2018 FIFA Men`s World Cup (MWC) in Russia and the 2019 FIFA Women`s World Cup (WWC) in France were examined retrospectively through video analysis. In the 2018 MWC, a total of 123 injury time-outs with 132 treatments occurred in 64 matches, while in the 2019 WWC, 142 incidents with 150 injured players were recorded in 52 matches. The incidence of stoppage time was higher in women than in men (81.2 vs. 56.8 per 1000 match hours, respectively, p = 0.004), and accordingly, women had a higher overall incidence of injury (IRR = 1.4 [95%CI = 1.1-1.8], p = 0.005). Despite women required more medical care during games, the substitution rate after the incidents was higher for men (27.3% to 15.3%, p = 0.02). Almost three-quarters of incidents for both sexes were sudden-onset contact injuries and the most common site was the lower limb. Although more frequent match incidents were seen in women`s football, the rate of completing the game without being substituted was higher than that of men. Obtaining insight into the medical intervention requirements of players during the course of a game will aid in the identification of injury-related behavioral patterns among players.